DECISION TREE BASED LOCALIZATION IN WIRELESS SENSOR NETWORKS - Kavitha, M.G.; SendhilNathan, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Localization in Wireless Sensor Network (WSN) plays a vital role in applications such as military, medical, healthcare, civil and environmental applications etc. Since all the sensor nodes in wireless sensor network are battery powered it is highly required to effectively utilize the sensor nodes in such a way that the lifetime of WSN is higher. Due to the limited availability of battery power in sensor nodes, energy consumption, computation speedup and memory consumption of localization algorithms are to be considered. In this paper a novel decision tree based approach (DTBL) for locating the nodes in WSN is discussed. The proposed approach is energy efficient in nature and high level of accuracy is obtained when compared with other localization techniques.